Politiques Publiques, Insertion Des Jeunes Et Secteurs d’Emplois d’Actualite - Pony Lucas (European Scientific Journal, ESJ, 2018)
This paper focuses on open public policies that are related to youth employment and hence to human capital or skills training. From the objective of this study, it is important to recognize that debates around public development policies, focused on external openness and youth employment, have always existed in both developed and underdeveloped countries. Inspired by all these debates, we were able to develop our hypothesis and, subsequently, an adequate methodology to verify them. This shows a causality between the variables: external openness, employment and qualifying training or public policy. Thus, we will start from the neoclassical economic theory that relates production, capital, and employment to develop our econometric model. We, therefore, found that it is appropriate to use VAR (value at risk) modeling to analyze the interrelationship between the variables: open access, human capital and employment. The data come from the World Bank, specifically from the "World Development Indicators" , which has earned us a longitudinal sectional study over the period from 1979 to 2014. It uses Word and Excel software to ensure the processing of our data as well as Eviews for the analysis of our data. In this way, we arrive at the result and the recommendations according to which it is necessary to upgrade the GESP (strategy documents for growth and employment in Cameroon). In their elaboration in August 2009, they were focused on the global economic crisis in providing, among other things, appropriate responses to the problems raised by the so-called crisis. This has also placed growth and employment in Cameroon at the center of their actions. To this end, the integration of young people should start from public policies according to the sectors of news and concerns of the jobs of subcontracting and the jobs of transition. It insists on the formations qualifying and, in the long run, the auto employment of the young people.